Of quantity and quality - Black, R. D. Collison (Statistical and Social Inquiry Society of Ireland, 1986)
In the social sciences generally, and in Economics in particular, one of the perennial themes of debate has been the merits and demerits of mathematical and statistical methods on the one hand and literary, philosophical and historical methods on the other. At the cost of some sacrifice of accuracy to brevity, I shall henceforth refer to the advocates and practitioners of the former approach as the quantifiers, and of the latter approach as the qualifiers.
Read before the Society 15th May 1986
Keywords: History of economic methodology; Qualitative methods; 314.15